Students' Difficulties in Reading Comprehension of Narrative Text at the Eleventh Grade of SMA Negeri 7 Padang - Latifah Nurmeina Azral; Dinovia Fannil Kher (Journal of English Language Teaching, 2023)
This study purposed to find out the difficulties faced by eleventh grade students of SMA Negeri 7 Padang in reading comprehension and to find out the factors that most causing the students’ difficulties in reading comprehension of narrative text. This study was conducted through a descriptive quantitative method. This sample was 40 students chosen by using simple random sampling. Moreover, the data were collected from using a reading comprehension test and by distributing questionnaire. The finding of this study indicated that the majority of students faced difficulties in reading comprehension of narrative text. The mean of students’ score from reading comprehension test was 49,7, it was categorized into less category. The difficulties faced by eleventh grade students were in identifying reference (67,5%), understanding meaning of word/ vocabulary (58,8%), determining main idea (52,5%), identifying generic structures (50,8%), finding specific/ factual information (50%), and making inference/ moral value (46%). Then, the factors that most causing students’ difficulties are lack of a good reading strategy (1,41), lack of knowledge about grammar (1,44), lack of vocabulary (1,60) and speed reading (2,50). These four factors were categorized into very low and low category.